Overdiagnosis in organised mammography screening in Denmark. A comparative study - Gøtzsche Peter C; Zahl Per-Henrik; Jørgensen Karsten J (BMC, 2009)
Abstract Background Overdiagnosis in cancer screening is the detection of cancer lesions that would otherwise not have been detected. It is arguably the most important harm. We quantified overdiagnosis in the Danish mammography screening programme, which is uniquely suited for this purpose, as only 20% of the Danish population has been offered organised mammography screening over a long time-period. Methods We collected incidence rates of carcinoma in situ and invasive breast cancer in areas with and without screening over 13 years with screening (1991-2003), and 20 years before its introduction (1971-1990). We explored the incidence increase comparing unadjusted incidence rates and used Poisson regression analysis to compensate for the background incidence trend, variation in age distribution and geographical variation in incidence. Results For the screened age group, 50 to 69 years, we found an overdiagnosis of 35% when we compared unadjusted incidence rates for the screened and non-screened areas, but after compensating for a small decline in incidence in older, previously screened women. Our adjusted Poisson regression analysis indicated a relative risk of 1.40 (95% CI: 1.35-1.45) for the whole screening period, and a potential compensatory drop in older women of 0.90 (95% CI: 0.88-0.96), yielding an overdiagnosis of 33%, which we consider the most reliable estimate. The drop in previously screened women was only present in one of the two screened regions and was small in absolute numbers. Discussion One in four breast cancers diagnosed in the screened age group in the Danish screening programme is overdiagnosed. Our estimate for Denmark is lower than that for comparable countries, likely because of lower uptake, lower recall rates and lower detection rates of carcinoma in situ.